The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/23259671211060023
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Minimal Clinically Important Difference on the Oxford Shoulder Instability Score in Patients Undergoing Arthroscopic Bankart Repair for Shoulder Instability

Abstract: Background: The literature on minimal clinically important differences (MCIDs) for patient-reported outcome measures assessing shoulder instability is limited, with none addressing the Oxford Shoulder Instability Score (OSIS). The OSIS was developed to provide a standardized method for assessing shoulder function after surgery for shoulder instability, and previous studies have demonstrated its high reliability, low interrater variability, and ease of administration. Purpose: To identify the MCID for the OSIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Only a few studies have attempted to define MCID values for anterior shoulder instability, all after arthroscopic Bankart repair and without considering PASS. 8,23,24 The present study is among the first to define clinically relevant states (MCID and PASS) across various PROs after open Latarjet. Park et al 23 calculated MCID for the Rowe and WOSI scores in 198 patients undergoing arthroscopic Bankart repair.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Only a few studies have attempted to define MCID values for anterior shoulder instability, all after arthroscopic Bankart repair and without considering PASS. 8,23,24 The present study is among the first to define clinically relevant states (MCID and PASS) across various PROs after open Latarjet. Park et al 23 calculated MCID for the Rowe and WOSI scores in 198 patients undergoing arthroscopic Bankart repair.…”
Section: Discussionmentioning
confidence: 94%
“…24 A recent study published in January 2022 reported MCID values using both anchor-based and distribution-based (0.20 effect size) methods for the Oxford Shoulder Instability Score, yielding values ranging from 7.7 to 8.6. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal clinically important difference was 8.5 for the ASES score, 51 9.7 for the Rowe score, 51 and 8.6 for the OSIS. 29 General satisfaction with the clinical outcomes of surgery was rated on a 5-level scale as very satisfied, satisfied, neutral, dissatisfied, and very dissatisfied. 49 Active shoulder ROM was measured, including forward flexion, external rotation (at both 0° and 90° of abduction), and internal rotation (recorded as the highest vertebral level that could be reached with the patient’s thumb).…”
Section: Methodsmentioning
confidence: 99%
“…20,27,28,40 Previous studies have defined MCID values for the Rowe score, the Western Ontario Shoulder Instability Index, and the Oxford Shoulder Instability Score after ABR. 11,29 Despite this, no studies have attempted to identify MCID values for the ASOSS score or PASS thresholds for the Rowe and ASOSS scores, which are 2 frequently used scores in glenohumeral instability research. 3 The MCID and PASS thresholds have demonstrated marked variation based on patient characteristics, type of intervention, preoperative diagnosis, and method of estimation, which may result in over-or underestimation of failure to improve.…”
mentioning
confidence: 99%